2017
DOI: 10.1016/j.jmii.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of double-stranded RNA viruses in Philippine Trichomonas vaginalis isolates

Abstract: This is the first study in the Philippines and one of the two reports worldwide to detect the four TVVs and their concurrent infection in a single T. vaginalis isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Various TVV were identified in six of the 18 T. vaginalis samples. Phylogenetic analyses in this study proposed monophyly in TVV1 and TVV2, but TVV3 and TVV4 appear paraphyletic ( 21 ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Various TVV were identified in six of the 18 T. vaginalis samples. Phylogenetic analyses in this study proposed monophyly in TVV1 and TVV2, but TVV3 and TVV4 appear paraphyletic ( 21 ).…”
Section: Discussionmentioning
confidence: 54%
“…The multiple viral infections in a single host has also been reported in the genera Totivirus and Victorivirus ( 1 ). The presence of several TVVs in a single culture may be due to the presence of multiple parasites that were infected with different TVVs or because of synchronous infection of TVVs in a single parasite ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition to these four TVV subspecies, additional strain diversity has been shown within each TVV species with numbers ranging from 14 to 35 different strains within each main TVV species found at a time. 44,45 Among the four distinct species of TVV known to be found in TV, TVV1 is the most prevalent, followed by TVV2 and TVV3, with TVV4 being the least prevalent. In terms of relatedness, TVV2 and TVV3 are more closely related to one another than to TVV1.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have found an association of TVV with TV isolates in various countries and at different prevalence rates. For countries with more than one study, the prevalence rates are reported as a range from the lowest rate to the highest: USA (30–100%), 11,12,15,1719,22,2527,36,44,4850,52,56,59 Cuba (55–100%), 14,34,38,5355 South Africa (81.9%), 33 Kenya (43.5%), 47 Brazil (60–100%), 3032,62 Iran (17–50%), 37,46 India (23.3%), 61 Egypt (20–35%), 57,60 China (50–100%), 51 Philippines (19%), 45 South Korea (13.6%), 35 Taiwan (50–100%), 13,23,24,3943 the Netherlands (50.4%), 58 and the Czech Republic (33–100%). 20,21,28,29…”
Section: Resultsmentioning
confidence: 99%
“…TVV seems to be transmitted only vertically, although some studies suggest a correlation between specific genetic polymorphisms and the entry and multiplication of TVV [42,44,47]. The presence of TVV influences negatively the growth rate of T. vaginalis in vitro if compared to uninfected protozoan isolates [48] and there is also evidence for lytic effects of TVV on T. vaginalis [49]. Almost 50 proteins are expressed differentially between TVV-infected and uninfected isolates, including metabolic enzymes, heat shock proteins (down-regulated in TVV-positive strains), and ribosomal proteins (up-regulated in TVV-positive strains) [50].…”
Section: Trichomonas Vaginalis and Trichomonasvirusmentioning
confidence: 99%